Analysing the Relationship Between Green Bonds and Sustainable Equity Markets: Sustainable Investing in Emerging Global Markets (Mutah Journal of Humanities and Social Sciences (MJHSS), 2025)
This research looks at tail risk contagion among environmentally friendly initiatives using data from July 2021 to August 2023. Tail risk is estimated using a novel asymmetric slope Conditional Autoregressive Value-at-Risk (CAViaR) and Time-Varying Parameter Vector Autoregressive (TVP-VAR) connectedness to explore the tail risk spillover. Additionally, the potential drivers of the connectedness network is measured over time. The result demonstrates a considerable degree of interconnection between Green Equities (GEs) and returns connected to sustainability, with sustainability-related indices playing a significant role and non-financial elements undergoing advancements. The level of interconnectedness fluctuates over time, with events such as the Russia-Ukraine War and COVID-19 exerting discernible effects. Investors and governments who are concerned about the environment may benefit greatly from the findings, which demonstrates that green bonds and stocks play distinctive roles and are seen differently in sustainable investing
Keywords: Green Bonds; Sustainable Equity Markets; Emerging Financial Markets; Environmental Responsibility; Financial Diversification.